2018
DOI: 10.3758/s13414-018-1635-3
|View full text |Cite
|
Sign up to set email alerts
|

Are there sex effects for speech intelligibility in American English? Examining the influence of talker, listener, and methodology

Abstract: Talker and listener sex in speech processing has been largely unknown and under-appreciated to this point, with many studies overlooking the possible influences. In the current study, the effects of both talker and listener sex on speech intelligibility were assessed. Different methodological approaches to measuring intelligibility (percent words correct vs. subjective rating scales) and collecting data (laboratoryvs.crowdsourcing)were alsoevaluated.Findings revealed that,regardless of methodology,thespokenpro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 55 publications
2
9
0
Order By: Relevance
“…For example, the degree of dispersion in individuals' vowel spaces—a reflection of the acoustic distinctiveness of individual vowels—predicted differences in intelligibility among the more‐intelligible talkers (a disproportionate number of whom were women), but only weakly predicted intelligibility across all 20 talkers. Similar findings are presented by Yoho et al (2019), who examined both intelligibility and subjective clarity ratings of sentences produced by 25 women and 25 men. They found large (~15%) differences between the average intelligibility of the women and men.…”
Section: Gender Effects In Speech Perception: a Review Of The Literaturesupporting
confidence: 81%
“…For example, the degree of dispersion in individuals' vowel spaces—a reflection of the acoustic distinctiveness of individual vowels—predicted differences in intelligibility among the more‐intelligible talkers (a disproportionate number of whom were women), but only weakly predicted intelligibility across all 20 talkers. Similar findings are presented by Yoho et al (2019), who examined both intelligibility and subjective clarity ratings of sentences produced by 25 women and 25 men. They found large (~15%) differences between the average intelligibility of the women and men.…”
Section: Gender Effects In Speech Perception: a Review Of The Literaturesupporting
confidence: 81%
“…That study [78] found no significant difference in single word intelligibility by gender in dysarthric participants with MS or PD nor in HCs. Females demonstrate a greater F0 variation when speaking [125], and it is known that a greater degree of F0 variation positively affects intelligibility [128][129][130]. However, a difference in F0 variability would more likely affect the intelligibility of sentences than the monosyllabic words used in the present study.…”
Section: Limitationsmentioning
confidence: 85%
“…The relatively little research that has been devoted to this question in healthy speakers has come to conflicting conclusions. Some studies found female voices to be more intelligible than males [123][124][125], some found male talkers to be more intelligible than female talkers [126], and some found male and female voices to be equivocal in terms of intelligibility [127]. There is only one study that we are aware of that addresses this question in neurologically impaired speakers.…”
Section: Limitationsmentioning
confidence: 99%
“…Identification rates for particular words depend on the talker's style of speaking. In addition to group differences that are known to affect speech intelligibility-speaker sex (Yoho et al, 2019) differences in language background (Bent & Bradlow, 2003;Clarke & Garrett, 2004) , and dialect variations (Clopper, 2021) -idiosyncrasies in speaking style that remain within the bounds of the accent and dialect with which the listener is most familiar can also affect speech identification (see McCloy et al, 2015) . Indeed, speech produced in a clear speaking style is identified more accurately than speech produced conversationally (Van Engen, 2017;Van Engen et al, 2012) , and speakers differ in the clarity of their speech (Smiljanić & Bradlow, 2005) .…”
Section: Variability Source #1: Characteristics Of the Talkermentioning
confidence: 99%